Consumer’s Perception towards Online Banking Services - Rupani, Raaizan; Qureshi, Aryan; Kumari, Sweta (International Journal of Finance Research, 2023)
In order to determine whether consumers would continue to use the Unified Payment Interface (UPI) for electronic payments, this study looks at the impact of consumer resistance-related issues. The findings suggest that privacy concerns and usage barriers are the two crucial factors to be addressed to break down consumer resistance towards continuing usage of UPI. It also covers consumer behavior, and the entire study is primarily oriented toward existing UPI customers. The basics, such as the workings of UPI and customer concerns, are explained in detail. Multiple Regression Analysis revealed that various factors significantly influence the adoption of cashless payment modes by online consumers and limit consumers' ability to pay for their purchases online.